Java 9 : building robust modular applications : master advanced Java features and implement them to build amazing projects - Lavieri, Edward D., Jr; Verhas, Peter; Lee, Jason (Learning path., 2018)
Mastering advanced features of Java and implement them to build amazing projects About This Book Take advantage of Java's new modularity features to write real-world applications that solve a variety of problems Explore the major concepts introduced with Java 9, including modular programming, HTTP 2.0, API changes, and more Get to grips with tools, techniques and best practices to enhance application development Who This Book Is For This learning path is for Java developers who are looking to move a level up and learn how to build robust applications in the latest version of Java. What You Will Learn Package Java applications as modules using the Java Platform Module System Implement process management in Java using the all-new process handling API Integrate your applications with third-party services in the cloud Interact with mail servers, using JavaMail to build an application that filters spam messages Use JavaFX to build rich GUI-based applications, which are an essential element of application development Leverage the possibilities provided by the newly introduced Java shell Test your application's effectiveness with the JVM harness See how Java 9 provides support for the HTTP 2.0 standard In Detail Java 9 and its new features add to the richness of the language; Java is one of the languages most used by developers to build robust software applications. Java 9 comes with a special emphasis on modularity with its integration with Jigsaw. This course is your one-stop guide to mastering the language. You'll be provided with an overview and explanation of the new features introduced in Java 9 and the importance of the new APIs and enhancements. Some new features of Java 9 are ground-breaking; if you are an experienced programmer, you will be able to make your enterprise applications leaner by learning these new features. You'll be provided with practical guidance in applying your newly acquired knowledge of Java 9 and further information on future developments of the Java platform. This course will improve your productivity, making your applications faster. Next, you'll go on to implement everything you've learned by building 10 cool projects. You will learn to build an email filter that separates spam messages from all your inboxes, a social media aggregator app that will help you efficiently track various feeds, and a microservice for a client/server note application, to name just a few. By the end of this course, you will be well acquaint...